The Role of Job Satisfaction in Mediating the Effect of Work Stress and Democratic Leadership on Employee Performance at Sushimi Restaurant in Bali - Ni Putu Ayu Tika Kurniawati; Ida Bagus Udayana Putra; I Made Suniastha Amerta (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
Employee performance is very important in managing a company. Performance is the result of the quality and quantity of work achieved by an employee in carrying out his duties according to the responsibilities assigned to them. Therefore, to be able to improve the performance of company employees, it is necessary to pay attention to the factors that affect performance. This study aims to determine the role of Job Satisfaction in mediating the effect of Job Stress and Democratic Leadership on Employee Performance at the Sushimi Bali Restaurant. The population in this study were all employees at the Sushimi Bali restaurant. The method used in this research is descriptive analysis method and inferential analysis using the Smart PLS (Partial Least Square) programs. The results showed that: (1) job stress has a negative and significant effect on employee performance, (2) job stress has a negative and significant effect on job satisfaction, (3) democratic leadership has a positive and significant effect on employee performance, (4) democratic leadership has a significant effect. positive and significant impact on job satisfaction, (5) job satisfaction has a positive and significant effect on employee performance, (6) job satisfaction does not mediate the relationship between job stress and employee performance, (7) job satisfaction does not mediate the relationship between democratic leadership and employee performance. It is suggested to the next researchers if they are going to conduct research on employee performance, they can take other variables besides job stress, democratic leadership and job satisfaction.